A short overview on mycophenolic acid pharmacology and pharmacokinetics. Issue 8 (28th June 2020) - Ferreira, Pâmela C. Lukasewicz; Thiesen, Flavia Valladao; Pereira, Andrea Garcia; Zimmer, Aline Rigon; Fröehlich, Pedro Eduardo
Abstract: Immunosuppressive therapy is used in solid organ transplant treatment, and mycophenolic acid (MPA) is one of the immunosuppressive drugs most used worldwide. It is a potent, selective, non‐competitive, and reversible inosine monophosphate dehydrogenase (IMPDH) inhibitor that acts to inhibit guanine synthesis. To improve solubility, MPA is used as the prodrug mycophenolate mofetil (MMF) or as an enteric‐coated mycophenolate sodium salt (EC‐MPS). It is metabolized into mycophenolic acid phenyl glucuronide (MPAG), the inactive and major metabolite, and into acyl glucuronide (AcMPAG), pharmacologically active. In kidney transplantation, combined immunosuppressive therapy with cyclosporine (CsA) and tacrolimus (Tac) is widely used, showing beneficial effects. This paper aimed to review papers published in the last two decades and discuss factors that can interfere with the pharmacokinetics of MPA. Data collected confirm that MPA plasma levels should be monitored to evaluate immunosuppressive therapy since pharmacokinetics can be influenced by factors such as interpatient variability, coadministration of other immunosuppressive agents, post‐transplant period, renal function, and dose. However, to perform drug monitoring, costs and facility may be limitations. Monitoring MPAG together with MPA would be a great improvement in therapy as it represents a big part of MPA levels and can be related to the increase of adverse effects.